First report of 'Candidatus Phytoplasma asteris' associated with witches'-broom disease of Cinnamomum camphora in China - Chen, Jianxin; Wu, Fengjinglin; Wu, Ziqiang; Yu, Zhixiang; Yang, Yalin; Ma, Huancheng; Wu, Jianrong (Plant disease, 2023)
Camphor tree (Cinnamomum camphora) has a wide distribution in the world and is mainly distributed in the South and southwest in China. It can be used as both a wood and a medicine, with high value in industry, medicine, and ecology. In May 2022, it was observed that the approximately ten to fifteen years old Camphor trees were exhibiting witches'-broom, ﻿small leaf morphology and chlorosis, and leaf drop in Panzhihua City, Sichuan Province, China. The witches'-broom symptoms consisted of many small branches with little leaves at the top of branches. It was named C. camphora witches'-broom disease (CCWB) and was found in some areas of Miyi, Yanbian, Renhe Xiqu and Dongqu counties. More than 28% of the plants were infected on the five areas surveyed. Total 100 samples were collected from five areas, with 15 symptomatic plants and 5 asymptomatic plants each area. The lateral stem tissues were observed under a scanning electron microscope (Hitachi S-3000N). The nearly spherical bodies were found in the phloem sieve cells of symptomatic plants. Total DNA extraction was conducted from 0.1 g tissue using the CTAB method (Porebski et al. 1997), ddH2O was used as the negative control, and Dodonaea viscose witches'-broom disease plants were used as the positive control. The nested PCR was employed to amplify the 16S rRNA gene (Lee et al. 1993; Schneider et al. 1993) and PCR amplicon of 1.2 kb were amplified (GenBank accessions OP662614; OP662615; OP662616). The direct PCR specific to the ribosomal protein (rp) gene yielded amplicons of approximately 1.2 kb with primer pair rp(I)F1A and rp(I)R1A (Lee et al. 2003) (GenBank accessions OP649592; OP649593; OP649594). The fragment from 25 symptomatic samples was consistent with the positive control, and asymptomatic plants were negative, confirming an association of a phytoplasma with the disease. A BLAST analysis of the 16S rRNA sequences of CCWB phytoplasma showed that it has a 99.44% similarity with Trema laevigata witches'-broom phytoplasma (GenBank accession MG755412). The rp sequence shared 99.59% identity with rapeseed phyllody phytoplasma (GenBank accession CP055264). An analysis with iPhyClassifier showed that the virtual RFLP pattern derived from the query 16S rDNA fragment of CCWB phytoplasma is most similar to the reference pattern of the 16Sr group I, subgroup B (OY-M, GenBank accession AP006628). The phytoplasma is identified as 'Ca. Phytoplasma asteris'-related strain belonging to sub-group 16SrI-B. The phylogenetic tree was constructed based on 16S rRNA gene and rp gene sequences by using MEGA version 6.0 (Tamura et al. 2013) with neighbor-joining (NJ) method and bootstrap support was estimated with 1000 replicates. The result indicated that the CCWB phytoplasma formed a subclade in 16SrI-B and rpI-B respectively. In addition, the plants were positive for the phytoplasma using nested PCR after grafting for 30 d in nursery conditions. It is noteworthy that the plants were seriously damaged by aphid, Psyllidae and Ceroplastes. It is speculated that the insects of ﻿Homoptera typically transmit phytoplasmas by feeding on plant sap, thus it is necessary to control aphids in order to control the C. camphora witches'-broom disease. To the best of our knowledge, Camphor tree is a new host plant of 'Ca. Phytoplasma asteris' in China. The newly emerged disease is a threat to Camphor tree production.